1990
DOI: 10.1038/sc.1990.74
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of early admission to an organised spinal cord injury care system

Abstract: SummaryPatients admitted to the University of Alabama Hospital between 1973 and 1985 were studied to determine the benefits, if any, of early admission to an organised, multidisciplinary spinal cord injury (SCI) care system. Patients admitted within 1 day of injury who received all subsequent care within the system were compared with patients who received their acute care services elsewhere and who were admitted to the system solely for rehabilitation. Both patient groups were comparable with respect to age, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 5 publications
0
41
0
Order By: Relevance
“…However, several studies have shown that lengths of hospitalization, costs of care, mortality rates, and medical complication rates are lower, whereas functional outcomes are better for patients treated at model systems than for patients treated elsewhere. [36][37][38][39] Therefore, given that only 10-15% of all new SCI in the United States each year are treated at model systems, overall outcomes are probably slightly overestimated by this study. 11 Moreover, it is possible that trends in model system treatment outcomes are not representative of trends in outcomes for patients treated elsewhere.…”
Section: Study Limitationsmentioning
confidence: 99%
“…However, several studies have shown that lengths of hospitalization, costs of care, mortality rates, and medical complication rates are lower, whereas functional outcomes are better for patients treated at model systems than for patients treated elsewhere. [36][37][38][39] Therefore, given that only 10-15% of all new SCI in the United States each year are treated at model systems, overall outcomes are probably slightly overestimated by this study. 11 Moreover, it is possible that trends in model system treatment outcomes are not representative of trends in outcomes for patients treated elsewhere.…”
Section: Study Limitationsmentioning
confidence: 99%
“…One of its primary goals was to evaluate the efficiency of such a system. 3 Although several studies have demonstrated that patients admitted to model SCI systems soon after injury tend to have better short-and long-term outcomes than patients whose admission to a model system is delayed, [4][5][6] information on acute care in non-model system facilities has been limited. Therefore, the original mission to evaluate the effectiveness of treatment programs at these nine model SCI systems of care compared with traditional care proved difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The relative shortage of spinal units (seven with a total 200 beds) does not permit all patients with spinal cord lesion to be admitted immediately to model centres where acute and rehabilitative interventions are integrated. 2 The lack of a standardised course between care in acute wards and a rehabilitation programme, means that the population arriving at the rehabilitation centres is very heterogeneous: after a wide range of time from the acute event, in different clinical conditions depending on previous management, 3 and possibly having undergone a selection connected to their aetiology.…”
Section: Introductionmentioning
confidence: 99%